Energy and macronutrient intake in adolescent sprint athletes: A follow-up study - Aerenhouts, D.; Deriemaeker, P.; Hebbelinck, M.; Clarys, P. (Journal of Sports Sciences, 2011)
Macronutrient intake, height, weight, and body composition of 60 adolescent sprint athletes were estimated every 6 months over 3 years. Seven-day food records were analysed based on the Belgian and Dutch food databanks. The age of participants at the start of the 3-year study was 14.8 ± 1.6 years for female athletes and 14.7 ± 1.9 years for male athletes. Girls and boys gained height (3.4 ± 4.6 cm and 5.9 ± 6.6 cm respectively) and weight (5.6 ± 3.5 kg and 8.7 ± 5.5 kg respectively), whereas percent body fat remained unchanged in both girls and boys (around 17.0% and 8.5% respectively). Mean protein intake of around 1.5 g/kg body weight was within recommendations on each occasion for both sexes. Carbohydrate intakes between 5 and 7 g/kg body weight support a training programme of moderate intensity. Total and saturated fat intakes were high at the start of the study (girls: 31.8 ± 3.5% and 12.2 ± 2.0% of energy intake; boys: 30.3 ± 4.6% and 12.0 ± 1.9% of energy intake) and it appeared to be difficult to achieve and maintain lower intakes. Consistent low fluid intakes around 40 ml/kg body weight were observed. General non-stringent advice for improvement of the diet resulted in significant favourable changes only for the consumption of wholegrain bread, vegetables, and soft drinks. Dietary habits of adolescent sprint athletes are not always according to guidelines and are relatively stable but repeated advice can induce moderate improvements.